Ostwald Ripening Process of Coherent β′ Precipitates during Aging in Fe0.75Ni0.10Al0.15 and Fe0.74Ni0.10Al0.15Cr0.01 Alloys - N. Cayetano-Castro; M. L. Saucedo-Muñoz; H. J. Dorantes-Rosales; Jorge L. Gonzalez-Velazquez; J. D. Villegas-Cardenas; V. M. Lopez-Hirata (Advances in Materials Science and Engineering)
The Ostwald ripening process was studied in Fe0.75Ni0.10Al0.15 and Fe0.74Ni0.10Al0.15Cr0.01 alloys after aging at 750, 850, and 950°C for different times. The microstructural evolution shows a rounded cube morphology (Fe, Ni)Al β′ precipitates aligned in the ferrite matrix, which changes to elongated plates after prolonged aging. The variation of the equivalent radii of precipitates with time follows the modified Lifshitz-Slyozov-Wagner theory for diffusion-controlled coarsening. Thermo-Calc analysis shows that the chromium content is richer in the matrix than in the precipitates which causes higher hardness and coarsening resistance in the aged Fe0.74Ni0.10Al0.15Cr0.01 alloy.